Mitochondrial iron supply is required for the developmental pulse of ecdysone biosynthesis that initiates metamorphosis in Drosophila melanogaster - Llorens, Jose Vicente; Metzendorf, Christoph; Missirlis, Fanis; Lind, Maria I. (Journal of biological inorganic chemistry, 2015)
Synthesis of ecdysone, the key hormone that signals the termination of larval growth and the initiation of metamorphosis in insects, is carried out in the prothoracic gland by an array of iron-containing cytochrome P450s, encoded by the halloween genes. Interference, either with iron-sulfur cluster biogenesis in the prothoracic gland or with the ferredoxins that supply electrons for steroidogenesis, causes a block in ecdysone synthesis and developmental arrest in the third instar larval stage. Here we show that mutants in Drosophila mitoferrin (dmfrn), the gene encoding a mitochondrial carrier protein implicated in mitochondrial iron import, fail to grow and initiate metamorphosis under dietary iron depletion or when ferritin function is partially compromised. In mutant dmfrn larvae reared under iron replete conditions, the expression of halloween genes is increased and 20-hydroxyecdysone (20E), the active form of ecdysone, is synthesized. In contrast, addition of an iron chelator to the diet of mutant dmfrn larvae disrupts 20E synthesis. Dietary addition of 20E has little effect on the growth defects, but enables approximately one-third of the iron-deprived dmfrn larvae to successfully turn into pupae and, in a smaller percentage, into adults. This partial rescue is not observed with dietary supply of ecdysone’s precursor 7-dehydrocholesterol, a precursor in the ecdysone biosynthetic pathway. The findings reported here support the notion that a physiological supply of mitochondrial iron for the synthesis of iron-sulfur clusters and heme is required in the prothoracic glands of insect larvae for steroidogenesis. Furthermore, mitochondrial iron is also essential for normal larval growth.
Gesehen am 02.06.2020